2022
DOI: 10.1007/s40477-022-00744-6
|View full text |Cite
|
Sign up to set email alerts
|

First trimester lower abdominal cysts as early predictor of anorectal malformations

Abstract: Introduction Prenatal ultrasound diagnosis of anorectal malformations (ARMs) is challenging and often missed as direct visualization of the anal sphincter is not routinely performed, plus the technique is operator-dependent and inaccurate, also in expert hands. Other indirect signs, such as rectosigmoid overdistension or intraluminal calcifications, are occasionally present in late pregnancy. The detection of a cyst of the lower abdomen in the first trimester may be an early sign of ARM. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
3
0
1
Order By: Relevance
“…According to Khalil et al 3 and Erculiani et al, 9 abdominal cysts detected in the first trimester are more frequent in male fetuses and more frequently associated with anorectal malformations, even if the cysts resolved during pregnancy as shown by Sepulveda et al, 4 which is consistent with our findings (two out of eight fetuses were diagnosed in the first trimester). Overall prognosis of these fetuses is poorer than that of those diagnosed in the third trimester, 3 especially if there are other associated abnormalities, 9 which is consistent with our findings (first‐trimester diagnosis, male fetuses, and association with other abnormalities as markers of poor prognosis).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…According to Khalil et al 3 and Erculiani et al, 9 abdominal cysts detected in the first trimester are more frequent in male fetuses and more frequently associated with anorectal malformations, even if the cysts resolved during pregnancy as shown by Sepulveda et al, 4 which is consistent with our findings (two out of eight fetuses were diagnosed in the first trimester). Overall prognosis of these fetuses is poorer than that of those diagnosed in the third trimester, 3 especially if there are other associated abnormalities, 9 which is consistent with our findings (first‐trimester diagnosis, male fetuses, and association with other abnormalities as markers of poor prognosis).…”
Section: Discussionsupporting
confidence: 92%
“…Gender distribution of fetal abdominal cysts changes throughout pregnancy: they are more frequent in male fetuses in the second trimester and in female fetuses in the third trimester, which is consistent with other larger studies, such as that by Ozkose et al 7 Husen et al 5 showed cyst regression in the third trimester for 67.9% of cases, which is higher than the figures reported by which is consistent with our findings (two out of eight fetuses were diagnosed in the first trimester). Overall prognosis of these fetuses is poorer than that of those diagnosed in the third trimester, 3 especially if there are other associated abnormalities, 9 which is consistent with our findings (first-trimester diagnosis, male fetuses, and association with other abnormalities as markers of poor prognosis).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations